Microwave assisted hydro-distillation of essential oils from fresh ginger root (Zingiber officinale Roscoe) - Racoti, Anca; Buttress, A.J.; Binner, Eleanor; Dodds, Chris; Trifan, Adrian; Calinescu, Ioan (Taylor & Francis, 2017)
A solvent free in situ microwave hydro-distillation method for extraction of essential oil from fresh ginger root it presented. Extraction was conducted in a TE10n single-mode microwave cavity and variable power 2 kW generator operating at 2.45GHz. The main extracted components identified by gas chromatography (GC) were Zingiberene, α-Curcumene, β-Sesquiphellandrene and α-Selinene. At energy inputs of 0.40 kWh/kg higher powers and shorter exposure times, crucially did not degrade the highly volatile components (α-Pinene and Camphene) despite providing the highest essential oil yields. Optimum processing conditions were found to be 1000W (0.40kWh/kg) for 5 min, for whole ginger root, where 0.35g oil/100g plant was obtained. This was compared to a yield of 0.2g/100g plant in 150 min in using conventional hydro-distillation and 0.3g/100g plant in 90 min using a multi-mode microwave cavity-based hydro-distillation.